Peer review of the pesticide risk assessment of the active substance urea - Álvarez, Fernando; Arena, Maria; Auteri, Domenica; Leite, Sofia Batista; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Cioca, Ana‐Andreea; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; et al. (EFSA journal, 2023)
The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Greece and co‐rapporteur Member State Finland for the pesticide active substance urea and the considerations as regards the inclusion of the substance in Annex IV of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of urea as an attractant of fruit fly Bactrocera oleae on olive crops. The reliable end points, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.